Rancang Bangun Sistem Penyiraman Tanaman Bibit Cabai Menggunakan Mikrokontroler Arduino - L M Samsu; Muhammad Saiful; B Nadila Nuzululnisa; Amri Muliawan Nur (Fakultas Teknik Universitas Hamzanwadi, 2026)
Manual watering of chili seedlings requires considerable time and effort and is often inconsistent in the amount of water provided, which can affect plant growth. This study aims to design and implement a prototype of a chili seedling watering system based on the Arduino Uno microcontroller that can operate automatically and manually. The research method used is a design and development method, which includes observation, system design, device assembly, programming, and system testing. The system uses a soil moisture sensor as the main controller, a DHT11 sensor to monitor environmental temperature, a relay to control the water pump, a toggle switch for manual operation, and a 16x2 LCD to display soil moisture, temperature, and pump status in real time. The test results show that in automatic mode, the pump activates when the soil moisture is below the threshold of 56% and stops when the moisture reaches 60%. In manual mode, the pump can be controlled directly using the toggle switch, while the LCD successfully displays all system parameters properly. The contribution of this study is the development of a simple and easy-to-use chili seedling watering prototype that helps maintain soil moisture stability and reduces dependence on manual watering